Structure and Morphology of Anthraquinone Triazene Films on Silicon Substrate - Shupenyuk, V. I.; Mamykin, S. V.; Taras, T. N.; Matkivskyi, M. P.; Sabadakh, O. P.; Matkivskyi, O. M. (Physics and Chemistry of Solid State, 2020)
An optimal imposition method of anthraquinone triazenes on silicon lining was selected. This allowed to create a nanometer film that can be used as dielectric aromatic buffer layers. A morphological research of triazene films shows the existence of delocalized globular anthraquinone macromolecular microformation on the background of triazene uneven layers. The oxidized surface of the triazene substrate is applied better than those without the oxide. This is caused by distribution of electron density in triazene which creates an additional Si/SiO2 coupling system and by presence of voluminous aromatic substituents which impairs the uniformity of film deposition and reduces its thickness.